Strongylides in Achatina (Lissachatina) fulica (Mollusca, Achatinidae) in Havana, Cuba - Rodríguez Pérez, José Alejandro; Meijides Mejías, Christian; Ramos Robledo, Alejandro; Pérez del Vallín, Vanessa; Mirabal Viel, Alejandro; Gómez Pérez, David; Castillo González, Willliam; Dorta Contreras, Alberto Juan; Martini Robles, Luiggi (Revista Cubana de Investigaciones Biomédicas, 2019)
Achatina (Lissachatina) fulica was introduced in Cuba in 2014 for african religious purposes and nowadays, mainly by human activity, it is widespread all over the country and, where besides a general nuisance for people it is a pest and also a public health concern, since it is one of the natural intermediate host of Angiostrongylus cantonensis, ethiological agent of the meningoencephalitis. As in Havana is experiencing the explosive phase of the invasion, LABCEL has been receiving samples of these molluscs for identification and search for Angiostrongylus cantonensis larvae. While examining samples of A. fulica different larvae were obtained, as strongylides found in the interior of the pallial cavity of A. fulica.This is the first report in San Miguel del Padron and Regla municipalities of the development of larvae in A. Fulica evidencing the health importance of this mollusc in the potential transmission of eosinophilic meningoencephalitis. Since the spread of A. fulica is pointed out in the literature as one of the main causative spread of the meningoencephalitis caused by A. cantonensis the authors emphasize the need of sanitary vigilance of snails and rats from vulnerable areas for A. cantonensis introduction as the port side areas like these municipalities.